PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK BERBASIS CERITA BERGAMBAR PADA ASPEK KETERAMPILAN MEMBACA SISWA MI MUHAMMADIYAH KAMPUNG BARU - Abdul Khaliq Ahmad; Tiara Putri Aziza; Nasrullah; Tarman A Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop learning media in the form of picture story-based comics to improve reading skills of elementary school students. The research used the Research and Development (R&D) method with the ADDIE model which consists of five stages: analyze, design, development, implementation, and evaluation. The research subjects were 30 fourth grade students of MI Muhammadiyah Kampung Baru. Data collection techniques included observation, interviews, documentation, questionnaires, and tests. The validation results showed that the media was declared valid with a material validation score of 94% and media validation of 86.66%. The practicality of the media is considered very good based on the average student questionnaire score of 93.71%. The effectiveness of the media was analyzed through the comparison of pretest and posttest scores, which showed an average increase from 53.3 to 86.7. The N-Gain calculation reached 0.71 with a high category. Thus, comic media based on picture stories proved to be valid, practical, and effective in improving the reading skills of elementary school students.